Peranan CSR dalam Mendorong Adaptasi Perubahan Iklim bagi Kelompok Agrosakamilenial untuk Mewujudkan Desa Tumpatan Nibung sebagai Agroekoedutourism: Pengabdian - Arisandy Aruan, Deasy; Hasudungan Sianturi, Ronald; Feri Tanjung, Ahmad; Nurhayati; Nurdiansyah, Hafiz; Khairunissa, Liandra; Dirhamsyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the capacity of the Agrosaka Milenial Community-Based Tourism Group group in adapting to climate change through the support of Corporate Social Responsibility (CSR). The program was implemented on October 25, 2025, in Tumpatan Nibung Village, Batang Kuis District, involving 30 farmers. The methods included climate change awareness sessions, training on climate adaptation technologies, an agroeco-edu-tourism planning workshop, and a Focus Group Discussion (FGD) to draft an adaptation action plan supported by CSR. The results indicate improved farmer awareness of climate risks, adoption of environmentally friendly technologies such as drip irrigation and organic fertilizer processing, and the development of an initial concept for agroeco-edu-tourism. It is concluded that CSR–farmer collaboration strengthens climate readiness and supports sustainable village development.